La vue et les matériaux. Le marbre dans l’Adoration du tombeau de saint Pierre de Vérone par Pedro Berruguete - VICENT DEBIAIS (Boletín del Museo del Prado)
Pedro Berruguete’s late 15th-century paintings for the conventual church of Santo Tomás in Ávila, now housed in the Museo del Prado, are among the hagiographic images that can be precisely associated with a historical context and a communicative intent. The commission for the three altarpieces that make up the group should be seen in the context of the institutions of the Inquisition. This article focuses on analysing a detail present on the panel of the tomb of Saint Peter of Verona, namely the marble of that tomb. This anecdotal detail, seemingly insignificant in terms of the work’s iconography, in fact plays an important role in the overall pictorial discourse employed in the conventual church of Santo Tomás.